TREE FLORA ON FRESHWATER WET HABITATS IN LOWLAND OF BORNEO: DOES WETNESS COOL THE SITES? - EIZI SUZUKI (REINWARDTIA, 2010)
SUZUKI, E. 2010. Tree flora on freshwater wet habitats in lowland of borneo: does wetness cool the sites?. Reinwardtia 13(2): 199-210. - The floristic records of lowland forests of Borneo in dry (not inundated) and wet (kerangas and peat swamp) habitats, and in montane forest of West Java were compared to clarify the characteristics of the flora in the lowland wet habitats. The data was flora of trees (DBH is equal to or more than 4.8 cm) in 12, 7, and 3 plots in dry lowland, wet lowland and mountain, respectively (20.9 ha in total). Plots in dry habitats had 42 to 53 families in 1 ha, except two plots on river banks (33 and 37 families). Plots in wet habitats and in mountain had 32 - 45 and 21 - 40 families, respectively. The clusters of plots in dendrogram using number of species in family mostly coincided with the difference in habitats. The preference for wet habitats existed in some families: Aquifoliaceae, Icacinaceae, Thymelaeaceae, Guttiferae, Myrtaceae, and Anacardiaceae though most families including Dipterocarpaceae and Euphorbiaceae had no tendency. Myristicaceae, Meliaceae, and Sapindaceae preferred dry habitats. Some species consisting of the flora of tropical mountains were found occasionaly in wet habitats of lowland though very rarely in dry habitats. There was a weak but singificant correlation between preference for wet habitats and abundance in Japanese tree flora of each family. These results suggest that the wet habitat where the forest floor is periodically filled with water has cooler environment than dry habitat, and families adapted cooler climate prefer the former.